Diagnóstico de las medidas alternativas de protección contra caídas en alturas, utilizadas por algunas constructoras de edificios en la ciudad de Bogotá D.C. (2014)
Work at height is a topic of great importance in all economic activities that perform their work implementing these practices for the development of their daily tasks; because it has been one of the main causes of death in Colombia. As time goes by, new ideas have been generated for the implementation of these activities in height, which has improved the condition of such work. In the area of ​​construction, Colombia still has a lot to implement if we compare it with countries such as Mexico and Chile, where more and more measures are being taken to address the issue and have reduced the dangers that this work generates. That is why With this work we will seek to identify all those practices that are developed in the construction of buildings in the city of Bogotá, to establish which of these comply with Colombian regulations and can be endorsed by the entities that verify this compliance. For this we will use methodologies such as : matrices, qualification of the risks and integration of the established norms for the work in height, looking for to find answers before the improvement and fulfillment in topics of work in height in the city of Bogota by means of the verification of these practices. This is how our result will be a diagnosis of the practices used and their verification against compliance or non-compliance with established standards.